Environmental Problem of Dirt Accumulation in Ukraine and its Impact on Labor Relations in the Sphere of Protection of Labor - Чанишева, Галія Інсафівна; Чанишева, Г. І.; Чанишева, Галия Инсафовна; Chanysheva, Haliia I.; Chanysheva, Galiya; Chanysheva, Galia І.; Шабанов, Роман Іванович; Шабанов, Р. І.; Шабанов, Роман Иванович; Shabanov, Roman І.; Коваленко, Олена Олександрівна; Коваленко, О. О.; et al. (FEPR, 2019)
The author raises an issue of the most serious environmental problems of modern Ukraine namely, catastrophic dirt accumulation in a worldwide context. Specific figures of this phenomenon and prospects as well as forecasts for near and middle-term outlook are shown. There has also been drawn a conclusion on real critical effect of a current situation on environmental safety and human health in Ukraine. The correlation between the increasing deterioration in the field of waste products of Ukraine and the necessity of normative strengthening of labor protection requirements (LP) has also been traced. It is recommended to pass a regulatory act on the issues of workers’ labor protection in the sphere of waste disposal and to establish the Inspection, in a Gostrud structure, on supervision and control over the observance of ecostandards at landfills and waste disposal sites of all types which may have significant impact on the solution of many problems in this sphere and to improve ecological future prospects for the country.

Автор порушує проблему найсерйозніших екологічних проблем сучасної України, а саме катастрофічного накопичення бруду у світовому контексті. Наведено конкретні показники цього явища та перспективи, а також прогнози на ближні та середньострокові перспективи. Також зроблено висновок про реальний критичний вплив поточної ситуації на екологічну безпеку та здоров'я людей в Україні. Також простежено взаємозв’язок між зростаючим погіршенням у сфері виробництва відходів України та необхідністю нормативного посилення вимог охорони праці. Рекомендується прийняти регуляторний акт з питань охорони праці працівників у сфері утилізації відходів та створити у структурі Державної служби України з питань праці Інспекцію з нагляду та контролю за дотриманням екологічних стандартів на звалищах та утилізації відходів усіх типів, які можуть мати значний вплив на вирішення багатьох проблем у цій сфері та покращити екологічні перспективи країни в майбутньому.
Chanysheva G. Environmental Problem of Dirt Accumulation in Ukraine and its Impact on Labor Relations in the Sphere of Protection of Labor / G. Chanysheva, R. Shabanov, O. Kovalenko // Ekoloji. – Vol. 28. - Issue 107. – FEPR, 2019. - P. 6001-6005.
Keywords: waste; domestic waste (DW); industrial waste (IW); solid domestic and industrial waste; hazardous waste; production and dirt accumulation; polymer waste; ecological crisis; waste industry; labor protection sphere; відходи; побутові відходи; промислові відходи; тверді побутові та промислові відходи; небезпечні відходи; виробництво і накопичення бруду; полімерні відходи; екологічна криза; промисловість відходів; сфера охорони праці; Research Subject Categories::LAW/JURISPRUDENCE